KEBUTUHAN MODAL KERJA PADA CV. CIPTA KARYA MANDIRI DI SAMARINDA - -, Julianti - (EKONOMIA, 2014)
The problems ofthis study, whether theworking capitalavailableto ensurethe smoothoperationalactivities.The purpose  of this research is to know and analyze large of working capital was needed on CV. Cipta Karya Mandiri in Samarinda,  To  guaranteed smooth activities of operational that business on  2013 and next  periods is object of selling good  and servisnd servicing was offered for consumer.Cognitive basicwriter utilize is working capital is one part of current asset which aptly get to be utilized to fund its operation firm without trouble its liquidity, which is constitute current asset excess upon it smooth book debt .Meanwhile this research Hypothesis that available Working Capital haven't secured oprasional's activity fluency. Analisis's tool in observational it there is three phases which is by use of formula account sell presage that utilize Metode Least Squars, accounting working capital rotation, so long working capital rotation, kecapetan is working capital rotation and accounts kebutusan working capital. On the calculation analyzer needed working capital on 2013 now, needed Rp. 431.523.720,-, used forecast of selling Rp. 1.294.571.160,-, and the assumed rate of rotation working capital same with 2012 yer is 3 times a yer, available working capitailable working capital  Rp. 313.016.500,-.Thus authors proposed the hypothesis was assumption the writer  that mention is estimated the working capital not sufficient to guarantee fluency operations activities at CV. Cipta Karya Mandiri in Samarinda in 2013 can be accepted.